TRANSFORMASI BISNIS TEMPO MEDIA GROUP MENUJU KONVERGENSI MEDIA - Ginjara, Yohanes Ray; Widiartanto, Widiartanto Widiartanto (Jurnal Ilmu Administrasi dan Bisnis, 2020)
The  media  industry  revolution  is  quite  large  and  the  results  are  already  visible.  Some  newspaper  and magazine publishers eventually closed and stopped production, while others still survived by preparing a new strategy of migrating publishing platforms to digital space, because the use of internet technology so rapidly and become a new culture. Tempo Media Group has made several changes in its business strategy. This  study  aims  to  describe  the  steps  taken  by  Tempo  Media  Group  in  carrying  out  its  business transformation  towards  media  convergence  during  2012-2015.  This  study  uses  descriptive  qualitative methods  to  find  out  in  depth  how  Tempo  Media  Group's  management  strategy  in  developing  Tempo.co online media. The results showed that Tempo Media Group used a strategy by transforming into digital media  and  by  continuing  to  maximize  revenue  from  the  print  media  business.  The  steps  taken  include improving the appearance of the Tempo.co site and strengthening the content. This convergence strategy must  be  accompanied  by  changes  in  behavior  of  all  corporate  entities.  Being  adaptive,  observing  each change intelligently, is a prerequisite for winning competition in the current era of digital media. Company management must to maintain a commitment to the values of independence, professionalism, and integrity in reporting news.